2023
DOI: 10.1002/iid3.798
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of SARS‐CoV‐2 infection in acute coronary syndrome and type 2 myocardial infarction (T2MI): Intertwining spread

Abstract: Coronavirus disease 2019 (COVID‐19) is a novel pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). It has been shown that SARS‐CoV‐2 infection‐induced inflammatory and oxidative stress and associated endothelial dysfunction may lead to the development of acute coronary syndrome (ACS). Therefore, this review aimed to ascertain the link between severe SARS‐CoV‐2 infection and ACS. ACS is a spectrum of acute myocardial ischemia due to a sudden decrease in coronary blood flow, ranging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 161 publications
0
6
0
Order By: Relevance
“… 104 Besides, retrospective studies showed that low levels of TC and LDL‐C could predict more severe involvement and increased risk of cardiovascular diseases due to changes. 105 , 106 , 107 A systematic review and meta‐analysis showed that lipid profile is associated with both the severity and mortality in Covid‐19 patients. Therefore, the lipid profile may be used for assessing the severity and prognosis of Covid‐19.…”
Section: Lipid Storm In Covid‐19mentioning
confidence: 99%
See 1 more Smart Citation
“… 104 Besides, retrospective studies showed that low levels of TC and LDL‐C could predict more severe involvement and increased risk of cardiovascular diseases due to changes. 105 , 106 , 107 A systematic review and meta‐analysis showed that lipid profile is associated with both the severity and mortality in Covid‐19 patients. Therefore, the lipid profile may be used for assessing the severity and prognosis of Covid‐19.…”
Section: Lipid Storm In Covid‐19mentioning
confidence: 99%
“…However, the Covid‐19 patients had lower TC and LDL‐C levels upon admission that would gradually recover as the patients' clinical condition improved 104 . Besides, retrospective studies showed that low levels of TC and LDL‐C could predict more severe involvement and increased risk of cardiovascular diseases due to changes 105–107 . A systematic review and meta‐analysis showed that lipid profile is associated with both the severity and mortality in Covid‐19 patients.…”
Section: Lipid Storm In Covid‐19mentioning
confidence: 99%
“…In addition, activators of the Nrf2 pathway can reduce exaggerated intra-renal AngII in diabetic patients and the development of diabetic nephropathy (Abdo et al 2015 ). The SARS-CoV-2 viral spike protein binds to ACE2, which aids viral entrance into the host cell (Al-Kuraishy et al 2023c , 2023e , 2022b ; Alsaidan et al 2023 ). In light of the probable elevation the expression of ACE2 by these drugs, there has been growing suspicion that ACE inhibitors and Ang II receptor blockers may raise the risk of the onset and severity of COVID-19 (Al-Kuraishy et al 2022h ).…”
Section: Mechanistic Role Of Nrf2 In Sars-cov-2 Infectionmentioning
confidence: 99%
“…[16][17][18][19]186] In addition to reducing the production of infectious virions, the inhibition of ER glucosidases prevents the entry of some viruses via a post-receptor-binding mechanism. [20][21][22][23] Therefore, dysregulation of RAS in Covid-19 could be the possible reason behind the reduction of Nrf2 activity. Thus, angiotensin receptor blockers (AT1R) may be beneficial in preventing OS and inflammatory reactions via upregulation of the Nrf2 pathway.…”
Section: Nrf2 and Inflammatory Signaling Pathways In Covid-19mentioning
confidence: 99%
“…[ 22 ] SARS‐CoV‐2 is highly identical to other CoVs like SARS and Middle East Respiratory Syndrome CoV (MERS‐CoV) and shares 80% and 60% genomic similarity. [ 23 ] In addition, SARS‐CoV‐2 is highly similar at the genomic level with bat CoV 96%. [ 24 ] SARS‐CoV‐2 is 20 times higher in use and binding ACE2 than other CoVs with succeeding downregulation of these receptors.…”
Section: Introductionmentioning
confidence: 99%